Reversal of reserpine-induced depression and cognitive disorder in zebrafish by sertraline and Traditional Chinese Medicine (TCM) - Zhang, Shuhui; Liu, Xiaodong; Sun, Mingzhu; Zhang, Qiuping; Li, Teng; Li, Xiang; Xu, Jia; Zhao, Xin; Chen, Dongyan; Feng, Xizeng (Behavioral and brain functions, 2018)
Background With increased social pressure, individuals face a high risk of depression. Subsequently, depression affects cognitive behaviour and negatively impacts daily life. Fortunately, the Traditional Chinese Medicine Jia Wei Xiao Yao (JWXY) capsule is effective in reducing depression and improving cognitive behaviour. Methods The constituents of JWXY capsule were identified by ultra-performance liquid chromatography and quadrupole time-of-flight mass spectrometry analyses. We analysed behaviours of depression-like zebrafish in the novel tank with an automatic 3D video-tracking system and conducted the colour preference test, as well detected physiological changes after sertraline and JWXY capsule treatments. Results Both sertraline and JWXY capsule rescued the decreased locomotive behaviour and depression phenotype of zebrafish caused by reserpine. JWXY capsule especially improved the inhibited exploratory behaviour caused by reserpine. In addition, with the onset of depressive behaviour, zebrafish exhibited alterations in cognitive behaviour as indicated by colour preference changes. However, compared with sertraline, JWXY capsule was more efficaciously in rescuing this change in the colour preference pattern. Moreover, an increased level of cortisol, increased expression of tyrosine hydroxylase (TH) and decreased monoamine neurotransmitters, including serotonin (5-HT) and noradrenaline, were involved in the depressive behaviours. In addition, sertraline and JWXY capsule rescued the depressive phenotype and cognitive behaviour of zebrafish by altering the levels of endogenous cortisol and monoamine neurotransmitters. Conclusions JWXY capsule was more effectively than sertraline in rescuing reserpine-induced depression and cognitive disorder in zebrafish. Potentially, our study can provide new insights into the clinical treatment of depression and the mechanism of action of JWXY capsule.